Conventional vs. Sharia Insurance: An Empirical Study on Financial Performance and Risk Management - Azizi, M. Riza; Hariono, Slamet; Dalail, Wahid (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
The Indonesian insurance industry, both conventional and Sharia insurance companies, has experienced significant growth in recent years. However, differences in operational frameworks, regulatory requirements, and investment restrictions raise questions about the financial stability and efficiency of these two insurance models. This study aims to compare the financial performance of conventional and Sharia insurance companies in Indonesia from 2022 to 2024 using the Early Warning System (EWS) and Risk-Based Capital (RBC) methods. Employing a comparative research design, this study utilizes secondary data from annual financial reports. The Mann-Whitney U-test is applied to examine statistical differences between the two types of insurance companies across eleven financial ratios. The results indicate significant differences in nine out of eleven ratios, namely the Solvency Margin Ratio, Underwriting Ratio, Claim Expense Ratio, Commission Ratio, Investment Return Ratio, Liquidity Ratio, Investment to Technical Reserve Ratio, Premium Growth Ratio, and RBC Ratio. The analysis demonstrates that Sharia insurance companies outperform their conventional counterparts across multiple metrics. While the Retention and Technical Reserve ratios show no significant variation, the overall findings substantiate the superior financial performance and risk management capabilities of Sharia insurance companies during the study period. These findings suggest that Sharia insurance companies demonstrate stronger financial performance compared to their conventional counterparts within the study period. The study highlights the financial resilience and risk management effectiveness of Sharia insurance, providing valuable insights for regulators, investors, and industry stakeholders.========================================================================================================ABSTRAK - Asuransi Syariah vs. Konvensional: Studi Empiris terhadap Kinerja Keuangan dan Manajemen Risiko. Industri asuransi di Indonesia, baik asuransi konvensional maupun syariah, telah mengalami pertumbuhan yang pesat dalam beberapa tahun terakhir. Namun, perbedaan dalam kerangka operasional, regulasi, dan batasan-batasan investasi memunculkan persoalan terkait stabilitas keuangan dan efisiensi dari kedua jenis asuransi tersebut. Penelitian ini bertujuan untuk membandingkan kinerja keuangan asuransi konvensional dan syariah di Indonesia pada periode 2022-2024 dengan menggunakan metode Early Warning System (EWS) dan Risk-Based Capital (RBC). Data penelitian berasal dari laporan keuangan tahunan yang kemudian dianalisis dengan desain penelitian komparatif. Untuk menguji perbedaan statistik antara kedua jenis asuransi tersebut, penelitian ini menggunakan Uji Mann-Whitney U terhadap sepuluh rasio keuangan EWS dan satu rasio RBC. Hasil penelitian menunjukkan adanya perbedaan signifikan pada sembilan dari sebelas rasio, yaitu Rasio Solvabilitas, Rasio Underwriting, Rasio Beban Klaim, Rasio Komisi, Rasio Pengembalian Investasi, Rasio Likuiditas, Rasio Investasi terhadap Cadangan Teknis, Rasio Pertumbuhan Premi, dan Rasio RBC. Hasil tersebut menunjukkan bahwa perusahaan asuransi syariah mengungguli asuransi konvensional dalam sebagian besar metrik yang diuji. Meskipun rasio Retensi dan Cadangan Teknis tidak menunjukkan variasi signifikan, temuan keseluruhan membuktikan keunggulan kinerja keuangan dan kemampuan manajemen risiko perusahaan asuransi syariah selama periode penelitian. Temuan ini menunjukkan bahwa asuransi syariah memiliki kinerja keuangan yang lebih kuat dibandingkan asuransi konvensional dalam periode penelitian. Studi ini juga menggarisbawahi stabilitas keuangan dan efektivitas manajemen risiko dalam asuransi syariah, memberikan wawasan yang berharga bagi regulator, investor, dan pemangku kepentingan industri.